The Effect Of Financial Self-Efficacy, Socioeconomic Status, And Locus Of Control On Financial Management Behavior Among Generation Z In West Bangko Barat - Kesi Kastiani Harahap; Eka Ermawati; Fenisi Resty (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study was motivated by the increasing consumptive behavior of Generation Z due to the rapid development of technology, social media, and the ease of digital transactions, which may affect financial management behavior. This condition requires Generation Z to manage their finances wisely in order to meet both present and future needs. The objective of this study was to analyze the influence of Financial Self-Efficacy, Social Economic Status, and Locus of Control on Financial Management Behavior among Generation Z in Bangko Barat District. This study employed a quantitative research method with a population of 3,301 Generation Z individuals and a sample of 312 respondents selected using the Isaac and Michael table. Data were collected through questionnaires using a Likert scale. The data were analyzed using validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and the coefficient of determination with the assistance of SPSS version 20. The results showed that, partially, Financial Self-Efficacy and Social Economic Status had a positive and significant effect on Financial Management Behavior, while Locus of Control had no significant effect on Financial Management Behavior. Simultaneously, Financial Self-Efficacy, Social Economic Status, and Locus of Control had a positive and significant effect on Financial Management Behavior. The Adjusted R Square value of 0.897 indicated that 89.7% of the variation in Financial Management Behavior could be explained by the three independent variables, while the remaining 10.3% was influenced by other factors outside this study. Self-confidence in financial management played a greater role in shaping Financial Management Behavior than Locus of Control. This study is expected to serve as a reference for the development of financial management knowledge and provide insights for Generation Z, educational institutions, and the government to improve financial management behavior for the broader community.